Sustainable neighbourhood transformation - Gruis, Vincent (IOS Press, 2013)
Examines the effects of demolition and replacement strategies on sustainability from different perspectives - an economic perspective: the market position and the value of the neighbourhoods, a social perspective: the levels of social capital and residential stability, and an environmental perspective: the energy efficiency.